2009
DOI: 10.1016/j.jnoncrysol.2009.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MgO on dielectric properties and electrical conductivity of ternary zinc magnesium phosphate glasses

Abstract: a b s t r a c tGlasses with composition ðZnOÞ 30 ðMgOÞ x ðP 2 O 5 Þ 70Àx (x = 5, 8, 13, 18 and 20 mol%) have been successfully prepared by the melt-quenching technique. The dielectric permittivity (e 0 ) and loss factor (e 00 ) were measured in the frequency range of 0.01 Hz to 1 MHz and in the temperature range of 303 to 573 K. From the results, there is evidence of dipolar relaxation occurring between 10 3 -10 6 Hz, while at low frequencies, the spectrum is dominated by dc conduction which was manifested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 28 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…51 The large loss at very low frequencies (Fig. 6) was caused by DC conduction losses, which was in agreement with the previous study of Khor et al 52 The increase in energy loss with increasing temperature can be attributed to relaxation and conduction losses, which increased more rapidly with temperature. At temperature ≤343 K, such conduction losses were less related to ion migration losses and became increasingly important at higher temperatures and low frequencies.…”
Section: Dielectric Studiessupporting
confidence: 91%
“…51 The large loss at very low frequencies (Fig. 6) was caused by DC conduction losses, which was in agreement with the previous study of Khor et al 52 The increase in energy loss with increasing temperature can be attributed to relaxation and conduction losses, which increased more rapidly with temperature. At temperature ≤343 K, such conduction losses were less related to ion migration losses and became increasingly important at higher temperatures and low frequencies.…”
Section: Dielectric Studiessupporting
confidence: 91%
“…The E a2 value for 20 mol % ZnO content is found to be the lowest. Khor et al, [30], reported that Zn(II) cation is able to occupy network-forming sites as well as interstitial positions in glasses in this region. Although the values of E a1 vary dramatically, there is certainly an increasing trend as the concentration of ZnO increases.…”
Section: The Dc-conductivitymentioning
confidence: 98%
“…Magnesium phosphate glasses [16] were studied to check the influence of the electrical properties of ternary zinc on magnesium oxide. The increase of magnesium oxide (MgO) concentration, leads to the participation of Mg 2+ or Ca 2+ ions in the interior structure of the glass.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the thermally-activated migration of free ions in the main glass structure. If the thermal energy is improved in the glass samples, then many charge carriers can overcome easily the attraction and diffuse long distances in the sample [16].…”
Section: Introductionmentioning
confidence: 99%